Molecular Characteristics of Geoffroy's Rousette Rousettus amplexicaudatus Based on Cytochrome C Oxidase Subunit I and Cytochrome b Genes - Kamilah, Santi Nurul; Jarulis, Jarulis; Sitompul, Aida Fitriani; Mardiah, Mifta; Ervinda, Mira; Khoirillah, Fanni; Lestari, Fitri Dwi; Zulkani, Dinda (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Background: Rousettus amplexicaudatus is widely distributed across Indonesia, including the Suruman Cave in South Bengkulu. Due to similarities in morphology within the Rousettus group, identification can be challenging. We conducted a molecular analysis using COI and Cytochrome b genes from mitochondrial DNA to explore its genetic traits. DNA was extracted from the blood tissue of seven individuals from the Suruman Cave population, and gene amplification was performed with 20 bp primers. Sequence data were analyzed using MEGA XI software. Results: As a result, characteristics of the COI gene, which is 897 bp in length, were characterized by a high frequency of base pairs Adenine-Thymine (55.5%) and Guanine-Cytosine (44.5%), with the majority of the DNA sequence exhibiting a high degree of conservation sites (97.8%). The average intrapopulation genetic distance based on the COI gene was 0.77%, with four specific sites for R. amplexicaudatus Suruman Cave. The Cytochrome b gene, which is 635 bp long, is characterized by Adenine-Thymine base pairs of 53.7% and Guanine-Cytosine of 46.3%. Cytochrome b is more conserved than the COI (99.1%). The average intrapopulation genetic distance based on the Cytochrome b gene is 0.3% and has no population-specific sites. Conclusions: Both sequences showed a consistent pattern in phylogenetic tree analysis, which suggests the Suruman population is the group of R. amplexicaudatus. Therefore, these sequences can be proposed as molecular markers for R. amplexicaudatus, particularly when compared to the whole sequences of the COI and cytochrome b.